2017
DOI: 10.1111/joic.12415
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and angiographic outcome of a single center, real world population treated with a dedicated technique of implantation for bioresorbable vascular scaffolds. The FAtebenefratelli Bioresorbable Vascular Scaffold (FABS) registry

Abstract: In a complex, all-comers real world population, BVS implantation with a specific, and standardized technique showed to be feasible, with acceptable mid-term angiographic and long-term clinical outcome.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2018
2018
2019
2019

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 18 publications
(24 reference statements)
0
5
0
Order By: Relevance
“…Malapposition, underexpanded device, late discontinuity and uncovered struts have been suggested as mechanisms for late stent thrombosis, pointing at the importance of the implantation technique in conditioning the long‐term results of BVS. In fact, adequate sizing, lesion preparation, postdilatation and the use of intravascular imaging for the optimization of the procedure, have been applied in most recent trials with more promising results . In the Outcomes of Absorb Bioresorbable Scaffolds with Improved Technique in an Expanded Patient Population (ABSORB IV) randomized trial, showed comparable results with the everolimus eluting BVS and DES in terms of TLF up to 1‐year follow‐up.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Malapposition, underexpanded device, late discontinuity and uncovered struts have been suggested as mechanisms for late stent thrombosis, pointing at the importance of the implantation technique in conditioning the long‐term results of BVS. In fact, adequate sizing, lesion preparation, postdilatation and the use of intravascular imaging for the optimization of the procedure, have been applied in most recent trials with more promising results . In the Outcomes of Absorb Bioresorbable Scaffolds with Improved Technique in an Expanded Patient Population (ABSORB IV) randomized trial, showed comparable results with the everolimus eluting BVS and DES in terms of TLF up to 1‐year follow‐up.…”
Section: Discussionmentioning
confidence: 99%
“…However, after the initial enthusiasm with the first cohorts of patients treated with BVS, 10 the availability of a longer-term angiographic follow-up evidenced phenomena of delayed reabsorption, associated with scaffold discontinuity and malapposition, increasing the risk of restenosis and thrombotic complications. 11,12 Indeed, procedural issues linked to the selection and preparation of the lesion and the stent implantation technique have been identified as limiting factors favoring such unfair angiographic results 13 and furthermore it is still unclear the application of the BVS in the settings of acute coronary syndrome (ACS), and especially in presence of a large thrombus burden, where both scaffolds and conventional DES are associated with problems of sizing, malapposition and plaque prolapse. The recent publication of new randomized clinical trials comparing PLLA-BVS with the newer generations of DES, [14][15][16] and enclosing data from a larger experience in the implantation technique and special subsets of patents, pave the way to the present most comprehensive metaanalysis, that aimed at evaluating the impact on the outcomes of BVS as compared to metallic DES.…”
Section: Introductionmentioning
confidence: 99%
“…At univariate analysis no relation was found with respect to ScT and newer antiplatelet used in both ACS (HR: 0.9, CI 95% 0.3–2.5, P = 0.8) and SCAD patients (HR: 1.6, CI 95% 0.3–10.1, P = 0.6), however, the relatively small number of events may have affected the results. Moreover, STEMI at presentation was found to be an independent predictor of ScT in a real word registry and it is interesting to notice that in our ACS population, among those who experienced ScT about 40% presented with STEMI at index procedure (13.3% of whom late comers >12 hr) highlighting he importance of patient selection to achieve good outcomes after BVS implantation.…”
Section: Discussionmentioning
confidence: 72%
“…Initially, Absorb BVS studies were limited to patients with stable angina and largely excluded complicated lesion characteristics [32]. After CE mark approval, real-world registry data began to highlight an excel of scaffold thrombosis (ScT) [33,34], particularly in the setting of acute coronary syndromes [35]. Finally, a comprehensive systematic review and meta-analysis including over 10,000 patients clearly reported a twofold increase in the rate of both myocardial infarction and definite or probable ScT compared with DES [36].…”
Section: The Poly-l-lactic Acid Bioresorbable Scaffold: a Lesson To Learn?mentioning
confidence: 99%